SURgical interventions with FEIBA (SURF): international registry of surgery in haemophilia patients with inhibitory antibodies. (3rd January 2013) - Négrier, C.; Lienhart, A.; Numerof, R.; Stephens, D.; Wong, W. Y.; Baghaei, F.; Yee, T. T.
Summary Factor VIII Inhibitor Bypassing Activity (FEIBA) can effectively achieve haemostasis in haemophilia patients with inhibitors. Further evaluation of FEIBA in surgical settings is of significant interest considering the relatively limited prospective data published to date. The aim of the study is to evaluate the perioperative efficacy and safety of FEIBA in haemophilia patients with inhibitors. Haemophilia patients with inhibitors who underwent surgical procedures and received FEIBA for perioperative haemostatic control were prospectively enrolled in an open‐label, noninterventional, postauthorization study [SURgical interventions with FEIBA (SURF)]. Outcome measures included haemostatic efficacy, safety, FEIBA exposure and blood loss associated with the perioperative use of FEIBA. Thirty‐five surgical procedures were performed at 19 centres worldwide in patients with congenital haemophilia A, congenital haemophilia B, or acquired haemophilia A. Haemorrhagic risk was severe in 37.1% (13 of 35) of the procedures, moderate in 25.7% (9 of 35) and mild in 37.1% (13 of 35). One moderate risk surgery was excluded from the efficacy analyses because it did not meet all protocol requirements. Haemostasis was judged to be 'good' or 'excellent' in 91.2% (31 of 34) of surgical procedures and 'fair' in 8.8% (3 of 34). Among the 12 adverse events, three were serious adverse events (SAEs), two of which were unrelated to FEIBA therapy; one SAE, a clot in an arteriovenous fistula, was deemed to be possibly related to therapy. This prospective investigation confirms that FEIBA can be safely and effectively used when performing surgical procedures in haemophilia patients with inhibitors.